Experimental and theoretical analysis for steel CHS K‐shaped joints stiffened with joint plates. (19th October 2021) - Peng, Peng; Zhang, Dachang; Cui, Mingcheng; Gao, Chenzhong
Summary: K‐shaped intersecting joint is a common type of joint in steel tubular structures, and its bearing capacity has an important effect on the structural performance. The relevant literatures and design codes are still lacking of the calculation theory on bearing capacity of steel tubular K‐shaped joints stiffened with joint plates, by which the effect of well‐welded stiffeners could not be considered. Four steel tubular K‐shaped joints with or without stiffened plates are designed, and their tests and nonlinear FEAs are carried out to investigate the bearing capacity characteristics, failure modes, and the effectiveness of stiffeners. The tests shown that the stiffened plates can significantly improve the bearing capacities of K‐shaped joints, and the plates should be looked as joint plates to evaluate its contribution to intensity, not just as stiffeners. Then, the parameter simulations and their influences on bearing capacities of stiffened K‐shaped joints are performed, in which the different sizes of chords, braces, and stiffened plates are selected. Compared with the test and simulation results, the bearing capacity of tubular K‐shaped joints with no stiffened plates could be calculated well by the theory in the relevant design codes. Using the superposition method of bearing capacities, the annular strength model and the calculation theory of stiffened tubular K‐shaped joints are proposed, in which the coefficients of multiparameter model are determined through regression analysis. Lastly, the theoretical bearing capacities of stiffened K‐shaped joints are analyzed and have good agreements with the test values. It can be concluded that the proposed calculation theory can be used to calculate the bearing capacity of stiffened K‐shaped joints with plates.